Faktor yang Mempengaruhi Kejadian Readmisi 30 Hari terhadap Pasien Congestive Heart Failure (CHF) - Ardiansyah Rasyid; Syahrul Syahrul; Takdir Tahir (Journal of Telenursing (JOTING), 2021)
This study aimed to identify the literature exploring the relationship between LACE scores (length of stay, acuity of admission, comorbidities and number of emergency room visits in the past six months) and health care costs for unplanned hospitalizations within 30 days of discharge, as well as the completeness of administrative data from the status of hospital medical records. The research method uses a literature review by tracing the results of publications between 2017-2020. The databases used were PubMed, ScienceDirect and ProQuest, with the results of 76 articles. The results identified eight studies that met the inclusion criteria and resulted in significant improvements using the LACE score in assessing and preventing readmission and lowering hospital costs. In conclusion, a predictor device application that uses electronic data or medical records is needed to manage CHF patients' readmissions. The use of the LACE score has the potential to aid clinical decisions as well as prevent future hospital readmissions. The higher the LACE score, the higher the readmission of CHF patients for 30 days, resulting in higher hospital costs. Keywords: Hospital Costs, Congestive Heart Failure, LACE Score